2022
DOI: 10.2147/prbm.s387241
|View full text |Cite
|
Sign up to set email alerts
|

Destination Attributes of Memorable Chinese Rural Tourism Experiences: Impact on Positive Arousal, Memory and Behavioral Intention

Abstract: Purpose There is a lack of research on the composition of destination attributes of memorable tourism experiences (MTEs) and their impact on tourist loyalty in Chinese rural tourism. Based on the extended SOR (stimulus-organism-response) theory, this study constructs a model of destination attributes (gastronomy, accommodation, physiography, and rural lifestyle) of MTEs on tourists’ recommend intention and revisit intention under the chain mediating effect of positive arousal and memory in Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 136 publications
1
1
0
1
Order By: Relevance
“…This result is consistent with Pan et al [166] and Hsu et al [58], who suggested that the accelerating rate of aging in China is responsible for the increase in potential tourists. The current study found that tourist revisits and recommendation behavior are demand drivers for RSHTUE development, consistent with the findings that satisfaction [99] and memorable travel experiences [100] influence revisit and recommendation behavior. Moreover, this study found that good social order at the destination is a supply driver for RSHTUE development.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is consistent with Pan et al [166] and Hsu et al [58], who suggested that the accelerating rate of aging in China is responsible for the increase in potential tourists. The current study found that tourist revisits and recommendation behavior are demand drivers for RSHTUE development, consistent with the findings that satisfaction [99] and memorable travel experiences [100] influence revisit and recommendation behavior. Moreover, this study found that good social order at the destination is a supply driver for RSHTUE development.…”
Section: Discussionsupporting
confidence: 89%
“…(4) Tourists' revisits and recommendations Factors influencing tourists' revisits and recommendation behavior include tourists' satisfaction [99], memorable travel experiences [100], and trust [101]. As a tourist (F15) said, "I have been coming to Zhongyuan Township every year from July to September for over 10 years.…”
Section: Social Drivers Of Demandmentioning
confidence: 99%
“…Gastronomi turizmi yalnızca zevk, eğlence ve heyecan sunan hedonik bir ürün değil, aynı zamanda turistlerin kendi kültürleri ile temas ettikleri diğer kültürler arasındaki farklılıkları keşfetmeleri, anlamaları ve paylaşmaları için bir araç olarak hizmet etmektedir (Antón vd., 2019). Gastronomi turizmi, turizm deneyiminin önemli bir parçasıdır ve coğrafi konumların gelenekleri, alışkanlıkları ve tarihi aracılığıyla yerel kültürü temsil etmektedir (Singh vd., 2022;Huang & Bu, 2022). Ayrıca, gıda ve mutfak bilimi, beslenme, sağlık, ekonomi, antropoloji, tarih, coğrafya ve sanat gibi alanlarla ilgili disiplinler arası bir kavram olarak nitelendirilmiştir (Seçuk vd., 2022).…”
Section: Gastronomi Turizmiunclassified